Integrating safety culture into OSH risk mitigation: a pilot study on the electrical safety - Zhao, Dong; Mccoy, Andrew; Kleiner, Brian; Feng, Yingbin (Journal of Civil Engineering and Management, 2016)
Efforts have been taken for years to minimize the occupational safety and health (OSH) risk, but the injury records remain a constant reason for worldwide concerns. Many firms often implement technology as an administrative hierarchy of control (HOC). However, technologies may also actively influence safe practices at the managerial level for administrative HOC. This research examines electrical safety hazards in the U.S. construction industry as a basis for, studying the feasibility of using technology to integrate safety culture into the administrative level of OSH risk mitigation. The researchers introduce the concept of “habitus”, which suggests one possibility for establishing a safety culture that increases workers’ safety performance and integrates into workers’ safety practices through cutting-edge information technology. A prototype application for OSH training based on mobile virtual reality (MVR) technology is demonstrated to help establish habitus in workers’ daily practices, and ultimately to mitigate OSH risks at the administrative level of construction projects. Results from a preliminary validation test strongly support human behavior influence and safe work knowledge comprehension by the prototyped application. Although this prototype is demonstrated as a pilot study of electrical safety, the application is not limited to this area and is scalable to other OSH risks.